2010
DOI: 10.1111/j.1398-9995.2010.02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratum corneum lipids, skin barrier function and filaggrin mutations in patients with atopic eczema

Abstract: Our results confirm previous observations of altered ceramide levels in AD, which however appear to show no clear relationship with FLG mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
218
5
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(255 citation statements)
references
References 38 publications
20
218
5
12
Order By: Relevance
“…This hypothesis is supported by a recent population-based study on adults which demonstrated associations of FLG mutations with 'dry skin' independent from the presence of AD, whereas associations with elevated IgE levels were only observed in atopic individuals [74]. More recent functional studies indicated that filaggrin mutations are associated with decreased levels of natural moisturizing substances, increased transepidermal water loss and increased skin pH, whereas they do not seem to contribute to the altered ceramide profile observed in AD [75,76]. However, more research is needed to elucidate the phenotypic characteristics caused by FLG mutations.…”
Section: Filaggrinsupporting
confidence: 62%
“…This hypothesis is supported by a recent population-based study on adults which demonstrated associations of FLG mutations with 'dry skin' independent from the presence of AD, whereas associations with elevated IgE levels were only observed in atopic individuals [74]. More recent functional studies indicated that filaggrin mutations are associated with decreased levels of natural moisturizing substances, increased transepidermal water loss and increased skin pH, whereas they do not seem to contribute to the altered ceramide profile observed in AD [75,76]. However, more research is needed to elucidate the phenotypic characteristics caused by FLG mutations.…”
Section: Filaggrinsupporting
confidence: 62%
“…AD olguların-da deri PH'sının arttığı ve bu artışın filagrin mutasyou taşıyan grupta anlamlı derecede yüksek olduğu gösterilmiş, bunun filagrin yıkım ürün-leri ile ilişkili olduğu belirtilmiştir. 15 Ancak, kesin olarak araştırmaların ortaya koyduğu önemli nokta, AD olgularında seramid yapısında ve profilinde sağlıklı populasyona göre değişikliklerin olduğu ve bunun da stratum korneumun su tutma kapasitesinin azalmasına, transepidermal su kaybının artmasına yol açtığıdır. 16 …”
Section: Derinin Bozulmuş Bariyer Fonksiyonuunclassified
“…The skin barrier defect is one of the primary events that initiate disease pathogenesis, allowing the entrance of numerous antigens into the epidermis in patients with AD (Onoue, et al, 2009, Osawa, et al, 2011. The FLG mutation carriers have demonstrated elevated TEWL (Jungersted, et al, 2010, Kezic, et al, 2008, basal erythema, skin hydration, increased skin pH (Jungersted, et al, 2010, Nemoto-Hasebe, et al, 2009), SC thickness (Nemoto-Hasebe, et al, 2009, impaired SC integrity upon repeated tape stripping (Angelova-Fischer, et al, 2011), and increased diffusivity of PEG 370 (Jakasa, et al, 2011) compared to healthy donors. Nevertheless, these alterations found in FLG mutation carriers are not consistently correlated with AD since AD patients without FLG mutation might also share some similar features.…”
Section: Filaggrin and Altered Skin Barrier Functionmentioning
confidence: 99%